Effects of yeast culture (Saccharomyces cerevisiae) on growth performance, serum biochemistry, rumen fermentation and microbiota of intake-restricted multiparous Suffolk sheep - Wang, Chuying; Niu, Yujie; Zhang, Peng; Lu, Qicheng; Yang, Jingquan; Chen, Ning; Zhang, Wenju (Frontiers in Microbiology, 2025)
IntroductionThis study evaluated the effects of yeast culture (YC) supplementation on growth performance, nutrient digestibility, serum parameters, rumen fermentation, and bacterial communities in intake-restricted multiparous Suffolk sheep, aiming to provide a theoretical basis for enhancing productivity.MethodsThirty multiparous Suffolk sheep (Suffolk♂ × Hu♀), with a mean body weight of 22 ± 0.5 kg, were arbitrarily assigned to three experimental groups: ad libitum feeding (AL), intake restriction (20% reduction, IR), and intake restriction with 30 g/d YC supplementation (20% reduction, IRY) groups (n = 10), and each sheep was housed separately.ResultsThe findings indicated that, compared to the IR group, the IRY group exhibited significantly increased average daily gain (ADG), net weight gain (NWG), digestibility of neutral detergent fiber (NDF) and acid detergent fiber (ADF), pH, total protein (TP), glucose (GLU), propionate, and immunoglobulin A (IgA) (p < 0.05), while feed-to-gain ratio (F/G) and acetate: propionate ratio (A: P) were significantly decreased (p < 0.05). Furthermore, differential feeding methods have significantly changed the composition of ruminal microbiota. The Shannon and Simpson indices were significantly higher in the IR and IRY groups compared with those in the AL group (p < 0.05), and the Chao1 index in the IRY group was significantly higher than that in the AL group (p < 0.05). The relative abundance of Prevotella in the IR group was significantly lower than that in the AL group (p < 0.05). The relative abundance of Ruminococcus in the IR and IRY groups was significantly lower than that in the AL group (p < 0.05). In contrast, the relative abundance of Bifidobacterium and Butyrivibrio was significantly higher in the IRY group compared with that in the AL and IR groups (p < 0.05).DiscussionThese results indicate that YC supplementation under intake restriction improves growth performance by enhancing apparent nutrient digestibility, improving rumen fermentation patterns, and increasing rumen bacterial community diversity in multiparous Suffolk sheep.